2020
DOI: 10.1111/bcp.14209
|View full text |Cite
|
Sign up to set email alerts
|

New psychoactive substances: Pharmacology influencing UK practice, policy and the law

Abstract: This review covers the last 20 years of UK drug control policy leading up to the recent Psychoactive Substances Act. It explores policy decision made in relation to MDMA and mephedrone that not only were associated with increased drug harms overall but also had a significant detrimental effect on the UK research base. The new UK legislation on synthetic cannabinoids and other novel psychoactive substances threatens to do the same, showing that there is still much to learn from the decisions of the past. In fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, the legislation has been criticised for the imprecise definition of psychoactivity, its blanket nature covering compounds with quite differing harm profiles, difficulties in enforcement, and exemptions that meant that popular NPS such as nitrous oxide can still be purchased. 4,12,13 Early evaluation of the Act suggested that whilst the availability of NPS had decreased, there was no evidence of a reduction in NPS-related harms. 14 By 2018, a total of 892 individual NPS, reported by 119 countries, were being monitored by the UNODC early warning system, 15 and by the end of 2018, over 730 NPS had been notified to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the legislation has been criticised for the imprecise definition of psychoactivity, its blanket nature covering compounds with quite differing harm profiles, difficulties in enforcement, and exemptions that meant that popular NPS such as nitrous oxide can still be purchased. 4,12,13 Early evaluation of the Act suggested that whilst the availability of NPS had decreased, there was no evidence of a reduction in NPS-related harms. 14 By 2018, a total of 892 individual NPS, reported by 119 countries, were being monitored by the UNODC early warning system, 15 and by the end of 2018, over 730 NPS had been notified to the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA).…”
Section: Introductionmentioning
confidence: 99%
“…However, the legislation has been criticised for the imprecise definition of psychoactivity, its blanket nature covering compounds with quite differing harm profiles, difficulties in enforcement, and exemptions that meant that popular NPS such as nitrous oxide can still be purchased. 4 , 12 , 13 Early evaluation of the Act suggested that whilst the availability of NPS had decreased, there was no evidence of a reduction in NPS-related harms. 14…”
Section: Introductionmentioning
confidence: 99%
“…6,8,9 In addition, clinicians treating patients presenting with acute toxicity and dependence related to the use of NPS often have less confidence in treating those patients compared to those who present with issues related to the use of established illicit drugs, despite the commonality of the issues seen. [10][11][12] In the European Union, the European Monitoring Centre for Drugs and Drug Addiction (EMCDDA) has developed new monitoring tools alongside their existing indicators with the hope that these will provide a more complete picture on the risks related to NPS. These new monitoring tools include syringe residue analysis, data on hospital emergency presentations from the European Drug Emergency Network Plus (Euro-DEN Plus) project, analysis of wastewater, drug checking services, and expanded web surveys.…”
mentioning
confidence: 99%
“…Previous data on the prevalence of use and harms associated with the use of illicit substances have traditionally focused on the frequency and volume of detection of substances in law enforcement and border seizures, drug‐related deaths, and utilisation of drug treatment services for drug dependency, along with data from animal and pre‐clinical studies . The exponential rise in the number and range NPS that have been detected and the rapidity by which substances become available has presented significant challenges in relation to our understanding of the prevalence of their use, how NPS are obtained by users, how we can detect the use of these substances, what the acute harms related to their use are, and how we respond to the potential public health risks posed by NPS . In addition, clinicians treating patients presenting with acute toxicity and dependence related to the use of NPS often have less confidence in treating those patients compared to those who present with issues related to the use of established illicit drugs, despite the commonality of the issues seen …”
mentioning
confidence: 99%
See 1 more Smart Citation